Outcome of Sorafenib Therapy in Advanced Hepatocellular Carcinoma (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer. It occurs most often in people with chronic liver diseases, such as cirrhosis caused by hepatitis B or hepatitis C infection. It is the fifth most common liver cancer globally and also a common cancer in Bangladesh. Treatment is difficult; however newer oral drug Sorafenib is available in our country which is promising.Objectives: To evaluate the efficacy of TKI Sorafenib on advanced and non-resect able primary HCC in Bangladeshi patients.Materials and Methods: This clinical trial was conducted on 38 diagnosed patients of advanced hepatocellular carcinoma (stage-3 and Child-Pugh Class-C) over a period of 3 years from May 2014 to July 2017 in the department of Oncology, CMH Dhaka. The patients receive Sorafenib 200-400 mg twice daily till disease progression ceases or increases and there are no unacceptable toxicities. Efficacy was observed in terms of overall survival, progressive free survival (PFS), drug compliance and common toxicities.Results: In 24 months of follow –up period from the date of Sorafenib taken, median overall survival was 7.73 months. The median overall survival was 8 months (range 8.13-27.43 months) in 42.4% patients. The median PFS is 3.5 months (range 1.2-5.8 months). Common toxicities found were anorexia, weakness, yellow colouration of skin and mucosa, HTN, rash and diarrhoea.Conclusion: In Sorafenib treated Bangladeshi advanced HCC patients, the median overall survival was found to be significant and compatible with some of the international publication.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 16-18